Perceived Changes in Communication as an Effect of STN Surgery in Parkinson's Disease: A Qualitative Interview Study - Emilia Ahlberg; Katja Laakso; Lena Hartelius (Parkinson's Disease)
The aim of the present study was to explore four individuals' perspective of the way their speech and communication changed as a result of subthalamic nucleus deep brain stimulation treatment for Parkinson's disease. Interviews of two men and two women were analyzed using qualitative content analysis. Three themes emerged as a result of the analysis. The first theme included sub-themes describing both increased and unexpected communication difficulties such as a more vulnerable speech function, re-emerging stuttering and cognitive difficulties affecting communication. The second theme comprised strategies to improve communication, using different speech techniques and communicative support, as well as trying to achieve changes in medical and stimulation parameters. The third theme included descriptions of mixed feelings surrounding the surgery. Participants described the surgery as an unavoidable dramatic change, associated both with improved quality of life but also uncertainty and lack of information, particularly regarding speech and communication changes. Despite negative effects on speech, the individuals were generally very pleased with the surgical outcome. More information before surgery regarding possible side effects on speech, meeting with a previously treated patient and possibly voice and speech therapy before or after surgery are suggested to facilitate the adjustment to the new speech conditions.